2000
DOI: 10.1002/1096-9861(20000807)423:4<579::aid-cne4>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the gene encoding SF‐1 alters the distribution of hypothalamic neuronal phenotypes

Abstract: The ventromedial nucleus of the hypothalamus (VMH) in mice first emerges as a histologically distinct cell cluster around embryonic day 17 (E17). The earliest known marker for cells destined to form the VMH is the orphan nuclear receptor, steroidogenic factor 1 (SF-1), which can be detected in the hypothalamic primordium by E11. Strikingly, the VMH is absent in newborn SF-1 knockout mice, suggesting that SF-1 is essential for the development of VMH neurons. We reported previously that the VMH can be identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
82
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 89 publications
(92 citation statements)
references
References 42 publications
8
82
0
Order By: Relevance
“…Previous studies proposed that the altered hypothalamic cytoarchitecture observed in sf-1 −/− mice might arise from the complete loss of VMN neurons due to cell death (Ikeda et al, 1995;Dellovade et al, 2000). However, TUNEL analysis revealed no apparent cell death in the presumptive VMN of both +/+ and −/− mice from E11 through postnatal day (P) 0 despite our ability to detect TUNEL-positive cells in the developing olfactory epithelium, as previously reported (Pellier and Astic, 1994;Voyron et al, 1999;and data not shown).…”
Section: Vmn Precursors Persist In Sf-1 −/− Neonatessupporting
confidence: 66%
See 3 more Smart Citations
“…Previous studies proposed that the altered hypothalamic cytoarchitecture observed in sf-1 −/− mice might arise from the complete loss of VMN neurons due to cell death (Ikeda et al, 1995;Dellovade et al, 2000). However, TUNEL analysis revealed no apparent cell death in the presumptive VMN of both +/+ and −/− mice from E11 through postnatal day (P) 0 despite our ability to detect TUNEL-positive cells in the developing olfactory epithelium, as previously reported (Pellier and Astic, 1994;Voyron et al, 1999;and data not shown).…”
Section: Vmn Precursors Persist In Sf-1 −/− Neonatessupporting
confidence: 66%
“…However, the presence of limited afferent projections from the mutant VMN area suggests that either terminal differentiation of a limited number of VMN neurons is not entirely dependent on SF-1 function, or alternatively, VMN precursors in mutant mice adopt neuronal fates of neighboring hypothalamic nuclei that also send axonal projections to the anterior hypothalamus. In this regard, Tobet and colleagues noted an expansion of neurons expressing ERα, galanin, and neuropeptide Y in the presumptive VMN of sf-1 −/− neonates (Dellovade et al, 2000). Normally, these peptides are selectively expressed in the neurons of lateral hypothalamus, dorsomedial nucleus, and arcuate nucleus, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research indicates that SF-1 play an important role in mammalian ventromedial nucleus development (Roselli et al, 1997;Fleming et al, 1999;Dellovade et al, 2000) and regulation of GTH expression in pituitary Ahmed, 1998;Bakke et al, 2001). We analyzed five regions of the carp brain including telecephalon, midbrain, cerebellum, and medulla oblongata, and found that SF-1 was expressed in the hypothalamus of both sexes (Fig.…”
Section: Discussionmentioning
confidence: 89%